Exploration of Modernity: Worship Reservation System at Rose of Sharon Church Salatiga Utilizing Flutter Framework - Hiuredhy, Davin Kurnia; Christanto, Henoch Juli; Christine, Christine; Sutresno, Stephen Aprius (Journal of Information Systems and Informatics, 2024)
Rose of Sharon Church (ROSC) Salatiga, as a rapidly growing spiritual community, faces challenges in managing the increasing number of congregants, especially during events and compliance with health protocols. This significant growth necessitates more effective attendance management to avoid overcrowding. This research addresses this need by developing the ROSC Worship Reservation application based on Progressive Web Apps (PWA) using the Flutter Framework. The application aims to simplify congregants' worship reservations, reduce crowds, and support church administrative tasks. The use of Flutter as the primary framework provides advantages in rapid development and a user-friendly interface. The results of the User Acceptance Test (UAT) show a high satisfaction rate, reaching 92%, regarding the application's functionality and user interface. Additionally, 84% of respondents state that the seating layout displayed by the application significantly aids in effectively choosing seats. It is hoped that the application will continue to provide benefits in managing congregational attendance systematically, efficiently, and in compliance with health protocols. The conclusion of this research emphasizes that the ROSC Salatiga Worship Reservation has successfully created an innovative solution to support church management amid the dynamic growth of congregational attendance.
Keywords: Worship Reservation System; Rose of Sharon Church; Flutter Framework; Progressive Web Apps; Mobile Application